Pemahaman Kader Posyandu tentang Pengolahan Bahan Pangan Pemberian Makanan Tambahan (PMT) Lokal: Studi Kebutuhan Pengetahuan dan Praktik untuk Peningkatan Kapasitas - rusyantia, anggun; Novika Juherman, Yulia; Muliani, Usdeka (NHM PRESS, 2024)
The supplementary feeding program based on local food has been implemented since 2023. Posyandu cadres are responsible for carrying out food processing for direct consumption by the target. This study was part of formative research, aimed to conduct a needs assessment to contribute to enhancing the competence of Posyandu cadres in processing Local Food-Based PMT in South Lampung Regency. This study employed a qualitative descriptive design, utilizing in-depth interviews. A total of five key participants, namely Posyandu cadres, were recruited for the study. Data triangulation was conducted with one program implementer from the Health Office and three Nutrition Officers from the Health Center. Four themes emerged from the results of the in-depth interviews: program knowledge, knowledge and practices of storing raw food, knowledge and practices of food processing, and knowledge and practices of serving processed PMT. The cadres demonstrated a strong understanding of the goals and targets of the Local Food-Based PMT program. However, their knowledge and practices related to the storage, processing, packaging, and serving techniques of local food-based PMT still require improvement. This research serves as a preliminary step for program developers to create educational strategies aimed at enhancing the competence of cadres, particularly in food processing techniques, to ensure the success of the Local Food-Based PMT program.